Analisis Kadar Protein, Total Volatile Base Nitrogen (TVB-N), dan Formalin pada Produk Perikanan : Tinjauan Kualitas dan Keamanan Pangan Berspektif Al-Qur’an: The Analysis of Protein Content, TVB-N, and Formalin in Fishery Products: A Review of Food Quality and Safety from the Perspective of the Qur'an - Noor Halimah; Mahmud Yunus Mustofa (Jurnal Ilmiah Pangan Halal, 2025)
Fish-based processed products represent an important source of animal protein in Indonesia. However, their quality and safety remain a concern due to the possible use of hazardous additives and the low awareness of halal compliance. This study aims to analyze protein content, Total Volatile Base Nitrogen (TVB-N), and formalin levels in various fish products and to evaluate their suitability with the halal–thayyib principles based on Qur’anic guidelines. The samples examined included fish balls, fish cakes, fish nuggets, dim sum, canned crab, milkfish, catfish, smoked manyung, salted squid, shrimp, and dried anchovies, obtained from traditional markets and small-scale processing units. Protein content was determined using the Kjeldahl method, while TVB-N measurement and formalin detection followed Indonesian National Standards (SNI). The results showed that several products met the protein requirements, whereas some samples contained excessively high TVB-N levels and unsafe formalin concentrations, posing potential health risks and violating halal food integrity. These findings highlight the need for improved hygienic processing, stricter quality control, and stronger consumer awareness regarding halal labels and nutritional transparency to ensure that fish products are safe, nutritious, and compliant with Islamic dietary principles.